Vitamin D 25OH deficiency in COVID-19 patients admitted to a tertiary referral hospital. Issue 4 (April 2021) - Cereda, Emanuele; Bogliolo, Laura; Klersy, Catherine; Lobascio, Federica; Masi, Sara; Crotti, Silvia; De Stefano, Ludovico; Bruno, Raffaele; Corsico, Angelo Guido; Di Sabatino, Antonio; Perlini, Stefano; Montecucco, Carlomaurizio; et al.
Summary: Background & aims: Great interest has been raised by the possible protective role of vitamin D in coronavirus disease 2019 (COVID-19), but objective data on 25(OH)vitamin D deficiency in hospitalized COVID-19 patients are not conclusive. The aim of this study was to determine the prevalence of 25(OH)vitamin D deficiency in COVID-19 patients admitted to an Italian referral hospital and explore its association with clinical outcomes and the markers of disease severity. Methods: In this single-center cohort study, 129 consecutive adult COVID-19 patients hospitalized in an Italian referral center were enrolled from March to April 2020. 25(OH)Vitamin D serum levels were assessed 48 h since hospital admission and categorized into: normal (≥30 ng/mL), insufficient (<30 - ≥20 ng/mL), moderately deficient (<20 - ≥10 ng/mL), severely deficient (<10 ng/mL). Results: The prevalence of 25(OH)vitamin D insufficiency, moderate deficiency and severe deficiency was 13.2%, 22.5% and 54.3%, respectively. 25(OH)Vitamin D deficiency (<20 ng/mL) was not associated with COVID-19 clinical features and outcomes. Unexpectedly, after adjusting for major confounders, a significant positive association between increasing 25(OH)vitamin D levels and in-hospital mortality (on a continuous logarithmic scale, odds ratio = 1.73 [95% CI, 1.11 to 2.69]; P = .016) was observed. Conclusions: Very low 25(OH)vitamin D levels were highly prevalent and suggestive of deficiency among our hospitalized severe COVID-19 patients, but low 25(OH)vitamin D levels were not associated with outcome variables. Whether 25(OH)vitamin D adequacy may influence clinical outcomes in COVID-19 and the unexpected correlation between higher 25(OH)vitamin D levels and mortality require further investigations by large intervention trials.